Assistance in Creating MSME Business Logo and Brand Design to Strengthen Business Image - Mentari Clara Dewanti; Virginia Mandasari (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
This community empowerment program focuses on enhancing the visual identity of Micro, Small, and Medium Enterprises (MSMEs) in Wonocolo District through guidance in logo and brand design. Many MSME owners still have limited understanding of how professional visual identity influences marketing effectiveness, causing their products to be less competitive despite good quality. The mentoring was carried out using a qualitative method, involving field observations, interviews. The results indicate that the program successfully improved participants’ knowledge of branding elements, including color schemes, typography, taglines, and the application of visual identity across promotional materials. Participants were also able to produce new logos that better reflect their business identity. Furthermore, the program strengthened their ability to use basic design applications and increased their confidence in applying branding strategies. Some challenges were encountered, including low digital skills, limited facilities, differences in creativity, and varied learning speeds. Nevertheless, these issues served as valuable input for future program enhancement. The program recommends organizing advanced design training, offering continuous assistance, and providing easily accessible learning resources to support consistent branding implementation across both offline and online media. Overall, this activity contributes to increasing MSMEs’ competitiveness by improving their branding and product appeal.